2013
DOI: 10.2147/cia.s42162
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical pharmacist recommendations in the geriatric ward of a Belgian university hospital

Abstract: ObjectiveTo evaluate the type, acceptance rate, and clinical relevance of clinical pharmacist recommendations at the geriatric ward of the Ghent university hospital.MethodsThe clinical pharmacist evaluated drug use during a weekly 2-hour visit for a period of 4 months and, if needed, made recommendations to the prescribing physician. The recommendations were classified according to type, acceptance by the physician, prescribed medication, and underlying drug-related problem. Appropriateness of prescribing was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
39
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 19 publications
14
39
0
3
Order By: Relevance
“…The observed reduction in MAI after physicians’ acceptance of pharmacist recommendations was comparable to other hospital studies that evaluated medication appropriateness in older adults using the MAI . However, this reduction is much lower than that observed from medication review studies in community settings .…”
Section: Discussionsupporting
confidence: 70%
“…The observed reduction in MAI after physicians’ acceptance of pharmacist recommendations was comparable to other hospital studies that evaluated medication appropriateness in older adults using the MAI . However, this reduction is much lower than that observed from medication review studies in community settings .…”
Section: Discussionsupporting
confidence: 70%
“…Clinical pharmacy is defined as the provision of patient-oriented pharmaceutical care, with the goals of maximising drug efficacy and minimising drug harm by preventing drug-related problems 1. Clinical pharmacy has been practised in most European countries for several years 2. The clinical and economic impact of clinical pharmacy has been addressed in many studies, and the value of clinical pharmacy has been shown by the improvement in both clinical and economic outcomes 3–8.…”
Section: Introductionmentioning
confidence: 99%
“…They analyse patients’ pharmacotherapy profiles in relation to their medical and laboratory data. When appropriate, they recommend drug therapy changes to physicians and nurses, and answer questions about drugs 2. Pharmacists routinely make clinical interventions in order to improve the health outcomes of patients 10.…”
Section: Introductionmentioning
confidence: 99%
“…Os medicamentos mais utilizados, segundo classificação ATC, foram do sistema digestório e metabólico, sistema cardiovascular, antiinfecciosos gerais para uso sistêmico e sistema nervoso, corroborando com Somers e colaboradores 19 . 25 mostraram que os medicamentos envolvidos com RAM induzidas por IM, de acordo com a classificação ATC, são do sistema nervoso (32,0%) e sistema cardiovascular (27,0%).…”
Section: Discussionunclassified